Combining Biomarkers to Predict Pregnancy Complications and Redefine Preeclampsia: The Angiogenic-Placental Syndrome. Issue 4 (April 2020) - Stepan, Holger; Hund, Martin; Andraczek, Theresa
Abstract : Placental dysfunction underlies a spectrum of perinatal pathologies, including preeclampsia and fetal growth restriction. Angiogenesis-related factors, including sFlt-1 (soluble fms-like tyrosine kinase 1) and PlGF (placental growth factor), play an important role in placental dysfunction; altered levels are detectable several weeks before onset of pregnancy complications. In vitro diagnostic tests for these biomarkers can improve early diagnosis and facilitate prediction of maternal and fetal outcomes. We assessed evidence for combining angiogenic biomarkers with other biomarkers or clinical parameters to predict maternal/fetal outcomes in pregnant women with placental dysfunction. Pooled information on placental perfusion (ultrasonography, mean arterial pressure), clinical characteristics, and biomarker levels (PlGF) can improve first-trimester prediction and preeclampsia diagnosis. Angiogenic factors (sFlt-1/PlGF ratio; PlGF alone) with or without clinical characteristics can facilitate second-/third-trimester prediction of early-onset and late-onset preeclampsia. A combination of increased sFlt-1/PlGF ratio and ultrasound can rule out early fetal growth restriction. The sFlt-1/PlGF ratio is also a reliable tool for discriminating between pregnancy-related hypertensive disorders, including superimposed preeclampsia and gestational hypertension. Analysis of angiogenic factors with or without uterine Doppler substantially improves sensitivity and specificity for predicting adverse outcomes and iatrogenic preterm delivery. We propose to extend the American College of Obstetricians and Gynecologists definition of preeclampsia in the future to include the combination of new-onset hypertension and new-onset of altered angiogenic factors (sFlt-1/PlGF ratio or PlGF alone). In summary, altered angiogenic biomarkers indicate placental dysfunction, and their implementation into clinical practice will help reduce the considerable burden of morbidity and mortality associated with adverse pregnancy outcomes as a consequence of angiogenic-placental syndrome. Abstract : Supplemental Digital Content is available in the text.